The Antithrombotic Efficacy of AT-1459, a Novel, Direct Thrombin Inhibitor, in Rat Models of Venous and Arterial Thrombosis - Cho, Jae-hyung; Yun, Chi-ho; Seo, Hyoung-sik; Koga, Takaki; Dan, Takashi; Koo, Bon-am; Kim, Hak-yeop (Thrombosis and Haemostasis, 2001)
The antithrombotic efficacy of AT-1459, a novel, direct thrombin inhibitor (Ki = 4.9 nM) was evaluated in rat models of venous thrombosis combined with a bleeding time test and arterial thrombosis.After drugs were given by i. v. bolus injection plus a continuous infusion, the ID50 (a dose that exhibits 50% inhibition of thrombus formation over each vehicle group) values of AT-1459, argatroban, and dalteparin were 0.04 mg/kg plus 0.04 mg/kg/h, 0.1 mg/kg plus 0.4 mg/ kg/h, and 13.0 IU/kg plus 26.0 IU/kg/h, respectively, in the venous thrombosis study. The BT2 (a dose that causes 2-fold prolongation of bleeding time over each vehicle group) values of AT-1459, argatroban, and dalteparin were 0.9 mg/kg plus 0.9 mg/kg/h, 1.0 mg/kg plus 0.6 mg/kg/h, and 345.5 IU/kg plus 691.0 IU/kg/h in the rat tail transection model. The ratios of BT2/ID50 of AT-1459, argatroban, and dalteparin were 22.5, 10.0, and 26.6, respectively.In a rat model of arterial thrombosis induced by topical FeCl2 application, intravenous administration of AT-1459, argatroban, and dalteparin improved the vessel patency significantly (P <0.01) at 0.6 mg/kg plus 0.6 mg/kg/h, 0.6 mg/kg plus 2.4 mg/kg/h, and 300 IU/kg plus 600 IU/kg/h, respectively.The oral antithrombotic effect of AT-1459 lasted for 6 after administering 30 mg/kg and improved the vessel patency significantly 1 h after administering the same dose in venous and arterial thrombosis models, respectively, with a rapid onset of action. Warfarin also inhibited thrombus weight and improved the vessel patency significantly after oral administration of 0.3 mg/kg for three consecutive days in the same study. The antithrombotic and hemorrhagic effects of all drugs studied were correlated with plasma concentration or clotting times.These results suggest that AT-1459 may be clinically useful as an orally available antithrombotic agent for the prevention of venous and arterial thrombosis.
Keywords: AT-1459; antithrombotic effect; bleeding time; clotting times